Hadis Nurmuhammad Sebagai Mahluk Pertama Studi Kritis Atas Al-Juz Al-Mafqud Min Al-Juz Al-Awwal Min Al-Mushannaf - M. Syukrillah (Rahmad : Jurnal Studi Islam dan Ilmu Al-Qur'an, 2024)
The belief on theNūr Muhammadas the beginning of creation and origin of all creatures in the universe is one of the main teachings in philosophical Sufism. This belief is based on a hadith attributed to 'Abdurrazzaq from Jabir bin 'Abdillah. The hadith is considered fake (maudhu') because it is not found in various writings of 'Abdurrazzaq and is only quoted in secondary hadith books with uncomplete sanad or disconnected of narration (ghair muttashil). Some people believe it to be valid, especially with the discovery of al-Juz al-Mafqud min al-Juz al-Awwal min al-Mushannaf which mention its sanadcompletely. This study describes the sanad and matan criticismand argumentum e silentio by intertextualitysearching for examining the validity claim of al-Juz al-Mafqud min al-Juz al-Awwal min al-Mushannaf.